PERAN WFP (WORLD FOOD PROGRAMME) DALAM MENGATASI KASUS KELAPARAN DI KOREA UTARA TAHUN 2006-2012 - Norhazwani "; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to describe the role of WFP (World Food Program) in addressing the case of famine in North Korea from 2006 to 2012. This study uses the framework of the theory of international organizations and the concept of food security. This research uses qualitative method by conducting library study. The role of WFP as an initiator is done by raising the issue of hunger and food security in North Korea to international forums to further determine what steps to take next. WFP serves as a determinator to determine how North Korea's famine problems are described using the concept of food security. The role of WFP as a facilitator is done by facilitating the needs of the North Korean people through the implementation of aid programs. WFP establishes assistance programs within the framework of urgent operations and recovery operations as well as project assistance such as food aid programs for workers and infrastructure development programs and agricultural support. Keywords: WFP, Hunger, North Korea, International Organization, food security